Memasarkan Tradisi: Klasifikasi Kegunaan Twitter dalam Festival Budaya - Yudo Hartono; Peni Zulandari (Sekolah Vokasi, Universitas Gadjah Mada, 2018)
The use of social media in promoting traditional selebration such as cultural festival is relatively new used by festival organizer. Twitter as one of social media can be effective if is used in cultural festival because it is perceived not only able to raise the audience awareness, but also able to involve many visitors to interact each others This research is focusing on how to describe the words that is used in Twitter and analizing the use of Twitter in promoting this festival. The analysis will be focused on word analysis and many comments will be processed by using computer software called Ripple 10. The result of this research can be used to evaluate, create decision to improve the festival quality in the future.